Behind the Scenes of the Great Strike by Hamilton Fyfe
"Behind the Scenes of the Great Strike by Hamilton Fyfe" [g0928001.jpg], n.d. Extract from 'Behind the Scenes of the Great Strike' explaining a police raid on the offices of the British Worker. TUC Organisation